Sistem Informasi Geografis Untuk UMKM Kuliner Pada Kelurahan Tanah Sereal - Lewenusa, Irvan; Gotama, Leonardo (STMIK Banjarbaru, 2023)
The Micro, Small and Medium-scale Enterprises (MSMEs) sector in Indonesia, especially in the city of Jakarta, is a key pillar for increasing income and creating jobs. MSMEs, including culinary businesses, stand out due to their affordable start-up capital and huge profit potential. To be successful in the culinary business, it is important to have an understanding of the market, a well-thought-out strategy plan, and choose the right location. Geographic Information Systems (GIS) play an important role in assisting aspiring culinary MSME entrepreneurs in choosing a suitable location and promoting their business in a useful way. This research adopts the Agile Scrum method with stages ranging from product backlog, sprint backlog, sprint, sprint review, to sprint retrospective. The GIS was designed using programming languages such as PHP, HTML, CSS, and the Laravel framework with the addition of a database. The results showed that the development of this GIS aims to provide assistance to the community in obtaining information about the location of Culinary MSMEs in Tanah Sereal Village. This system is designed so that it can be accessed and used easily by various parties. The conclusion of the research emphasizes the importance of developing GIS with suggestions for expanding regional coverage, adding MSME categories, improving the interface (UI), and adding features that make it easier for users. Thus, the implementation of GIS on culinary MSMEs in Jakarta City is expected to make a positive contribution to local economic development, create jobs, and provide easy access to information to the community.Keywords: MSMEs, Geographic Information System; Culinary; ScrumÂ AbstrakBidang usaha skala Mikro, Kecil, dan Menengah (UMKM) di Indonesia, terutama di Kota Jakarta, menjadi pilar utama untuk meningkatkan pendapatan dan menciptakan lapangan kerja. UMKM, termasuk bisnis kuliner, menonjol karena modal awal yang terjangkau dan potensi keuntungan yang besar. Untuk meraih kesuksesan dalam bisnis kuliner, penting memiliki pemahaman pasar, rencana strategi yang matang, dan memilih lokasi yang tepat. Sistem Informasi Geografis (SIG) berperan penting dalam membantu calon pengusaha UMKM kuliner dalam memilih lokasi yang sesuai serta mempromosikan usaha mereka secara berguna. Penelitian ini mengadopsi metode Agile Scrum dengan tahapan mulai dari product backlog, sprint backlog, sprint, sprint review, hingga sprint retrospective. SIG dirancang menggunakan bahasa pemrograman seperti PHP, HTML, CSS, dan framework Laravel dengan penambahan database. Hasil penelitian menunjukkan bahwa pengembangan SIG ini bertujuan untuk memberikan bantuan kepada masyarakat dalam memperoleh informasi mengenai lokasi UMKM Kuliner di Kelurahan Tanah Sereal. Sistem ini dirancang agar dapat diakses dan digunakan dengan mudah oleh berbagai pihak. Kesimpulan dari penelitian menekankan pentingnya pengembangan SIG dengan saran-saran perluasan cakupan daerah, penambahan kategori UMKM, peningkatan tampilan antarmuka (UI), dan penambahan fitur-fitur yang mempermudah pengguna. Dengan demikian, implementasi SIG pada UMKM kuliner di Kota Jakarta diharapkan dapat memberikan kontribusi positif dalam pengembangan ekonomi lokal, menciptakan lapangan kerja, dan memberikan kemudahan akses informasi kepada masyarakat.Â